An exclusive cache replacement policy based on read priority and dynamic sliding. (2017) - Dash, Banchhanidhi; Swain, Debabala; Paikaray, Bijay K.
The conventional cache replacement algorithms have massive hardware cost with ambiguous logic and measurability. Increasing the cache levels do not give a better solution for the hardware complexity and performance issues in multi-core processors. Rather number of read misses on executing the complex memory intensive program can increase the execution time in multi-core processors. This paper proposes a new way of cache replacement policy weight-based read priority replacement (WRPR), which works on the read priority of a cache line in all levels of cache. By making it read prior instead of write, the cache lines with more read access are highly weighted. During replacement, the cache eviction is done from dynamic logical cache regions based on its weight. The algorithm performance is tested using multi-core cache simulator with different benchmark workloads in the SMPCache simulator. The proposed replacement policy can work on any exclusive cache level in a multi-level hierarchy. It shows an improved performance from the hit rate context.